FSS on energy saving glass for rf communication enhancement in modern building - Najihah Zakaria; S. N. Azemi; P. J. Soh; C.B.M. Rashidi; A Abdullah Al-Hadi (Institute of Advanced Engineering and Science, 2019)
The use of energy saving glass has become very popular in the modern day building design. This energy saving property is achieved by applying a very thin tin oxide (SnO2) coating on one side of the glass. This coating can provide good thermal insulation to the buildings by blocking infrared rays while being transparent to visible part of the spectrum. Drawbacks of these energy saving windows is that it also attenuates the transmission of useful microwave signals through them. These signals fall within the frequency band of 0.8GHz to 2.2GHz. In order to pass these signals through the coated glass, the use of aperture type frequency selective surface (FSS) has being proposed. In the present work, SnO2 thin film with FSS structure was fabricated. Microwave transmission through SnO2 coated glass with FSS structure was also analyzed using network analyzer. The result of computer simulation was confirmed and consistent with the network analyzer results that showed the improvement of SnO2 coated glass with the FSS structure.